# ~/Blog

## Brandon Rozek

PhD Student @ RPI studying Automated Reasoning in AI and Linux Enthusiast.

# Lean 4 Tutorial

Published on

14 minute reading time

Lean is an interactive theorem prover created by Microsoft. In 2021, they performed a major transition from Lean 3 to Lean 4. This transition changed the syntax and tactics used within proofs and caused major library developers such as Mathlib to transition.

Last year I wrote a Lean 3 tutorial which showcases how to go about constructing proofs for several small problems. After revisiting Lean 4 recently, I decided that Mathlib support is comprehensive and stable enough to make the switch.

This post is the same as the Lean 3 tutorial that I wrote last year, except that the examples have been updated to the latest syntax.

## Propositional Logic (Intuitionist Fragment)

To prove something in Lean, we need to construct an object of that type.

### Conjunctive Introduction

To start off let us prove the statement $P \wedge Q$ given both $P$ and $Q$ individually.

example {p q : Prop} (H_p : p) (H_q : q) : (p ∧ q) := by
exact show p ∧ q from And.intro H_p H_q


This shows an application of conjunctive introduction. We created the object $P \wedge Q$ by applying the theorem And.intro to both hypotheses H_p which contains $P$ and H_q which contains $Q$.

Another way of going about this proof is by transforming the goal to another equivalent one.

example {p q : Prop} (H_p : p) (H_q : q) : (p ∧ q) := by
constructor
case left =>
exact show p from H_p
case right =>
exact show q from H_q


In this proof, we make use of the constructor tactic. Given a conjunctive goal $P \wedge Q$, this tactic replaces it with two subgoals $P$ and $Q$. We can then apply the hypotheses to solve the problem.

### Conjunctive Elimination

Given the proof of $P \wedge Q$, we can derive $P$ from it.

example {p q : Prop} (H_pq : p ∧ q) : p := by
exact show p from And.left H_pq


In the example above, we apply the inference And.left to be able to derive the left side of a conjunct. Similarly to the last inference rule, there is a tactic based way to go about it. Tactic based methods are generally more prevalent within the ITP community.

example {p q : Prop} (H_pq : p ∧ q) : p := by
cases' H_pq with H_p H_q -- p, q
exact show p from H_p


Given a conjunctive hypothesis, the cases' tactic will create two new hypothesis from it. The two labels after the with is to specify the names of these hypotheses. The string -- denotes the start of a comment; I left a small comment to remind me the ordering of the conjuncts.

### Disjunctive Introduction

Given any statement $P$, we can introduce an arbitrary formula as a disjunct. More intuitively, if Jarold is above the age of 10, then he is above the age of 10 or he likes lollipops. It does not change the truth value of the statement.

The inference based way of representing this is as follows:

example {p q : Prop} (H_p : p) : (p ∨ q) := by
exact show p ∨ q from Or.intro_left q H_p


In the more popular tactic based notion. We use the tactic left or right to denote which side we’re going to attempt to prove. If we’re trying to prove $P \vee Q$ and we have $P$ then we will prove the left side.

example {p q : Prop} (H_p : p) : (p ∨ q) := by
left
exact show p from H_p


### Disjunctive Elimination

The form of disjunctive elimination included in Lean is more commonly known as proof by cases. That is if you know either $A$ or $B$ is true. That is, $A \vee B$. And, you can derive $C$ from $A$ as well as $C$ from $B$. Then it doesn’t matter which of $A$ or $B$ is true, because you can derive $C$ regardless.

Wikipedia has a nice intuitive example:

If I’m inside, I have my wallet on me.

If I’m outside, I have my wallet on me.

It is true that either I’m inside or I’m outside.

Therefore, I have my wallet on me.

To achieve this in Lean using the inference based approach.

example {p q r : Prop} (H_pr : p → r) (H_qr : q → r) (H_pq : p ∨ q) : r := by
exact show r from Or.elim H_pq H_pr H_qr


Alternatively, via the tactic based approach

example {p q r : Prop} (H_pr : p → r) (H_qr : q → r) (H_pq : p ∨ q) : r := by
cases' H_pq with H_p H_q
case inl =>
-- Assume p, apply modus ponens with H_pr
exact show r from H_pr H_p
case inr =>
-- Assume q, apply modus ponens with H_qr
exact show r from H_qr H_q


## Negation

Traditional interactive theorem provers such as Coq focused on the constructivist approach to theorem proving. This allows them to export proofs as programs in OCaml. Lean places less of an emphasis on this approach and instead supports the proof by contradiction style you see in classical theorem proving.

For this tutorial, I decided to make this distinction explicit by declaring a new axiom for the law of excluded middle. By default, Lean has the axiom of choice which they use to prove the law of excluded middle through the proof Classical.em.

In other words, if you want to perform a proof by contradiction, don’t use the techniques shown in this section and instead use the by_contra tactic or directly use Classical.em.

Declare the axiom of law of excluded middle:

axiom LEM {p : Prop}: p ∨ ¬ p


### Negation Introduction

For negation introduction, let’s say we have some proposition $P$. If we can use $P$ to derive a falsity, let’s say $Q \wedge \neg Q$ then $P$ must be false. That is, we introduce a negation to make it $\neg P$.

The structure of the proof will a proof by cases on the law of exclude middle.

lemma negation_intro {p q : Prop} (H_pq : p → q) (H_pnq : p → ¬q) : ¬p := by
have H_LEM : p ∨ ¬p := LEM

-- Assuming ¬p derive ¬p
have H_npp : ¬p → ¬p := by
intro (H_np : ¬p)
exact show ¬p from H_np

-- Assuming p derive ¬p
have H_pp : p → ¬p := by
-- Use hypotheses to obtain q and ¬q
intro (H_p : p)
have H_q : q := H_pq H_p
have H_nq : ¬q := H_pnq H_p

-- We can derive falsity from a direct contradiction
have H_false : False := H_nq H_q

-- You can derive anything from false
have H_UNUSED: p ∧ ¬p := False.elim H_false

-- Including what we want, ¬p
exact show ¬p from False.elim H_false

-- By proof by cases, we derive ¬p
exact show ¬p from Or.elim H_LEM H_pp H_npp


Lean can tell us which axioms our proof depends on as well.

#print axioms negation_intro


This returns 'negation_intro' depends on axioms: [LEM].

Alternatively, the tactic based approach

example {p q : Prop} (H_pq : p → q) (H_pnq : p → ¬q) : ¬p := by
have H_LEM : p ∨ ¬p := LEM
cases' H_LEM with H_p H_np

case inl =>
have H_q : q := H_pq H_p
have H_nq : ¬q := H_pnq H_p
have H_false : False := H_nq H_q
exact show ¬p from False.elim H_false

case inr =>
exact show ¬p from H_np


As I mentioned before, we do not have to explicitly declare the axiom of excluded middle. Instead we can make use of Lean’s builtin classical reasoning.

example {p q : Prop} (H_pq : p → q) (H_pnq : p → ¬q) : ¬p := by
by_contra H_p
have H_q : q := H_pq H_p
have H_nq : ¬q := H_pnq H_p
exact show False from H_nq H_q


### Double Negation Elimination

One common representation of negation elimination is to remove any double negations. That is $\neg \neg P$ becomes $P$.

We’ll similarly show this by performing a proof by cases on the law of excluded middle.

example {p: Prop} (H_nnp : ¬¬p) : p := by
have H_LEM : p ∨ ¬p := LEM

-- Assuming ¬p derive p
have H_np2p : ¬p → p := by
intro (H_np : ¬p)
-- ¬p and ¬¬p are a direct contradiction
have H_false : False := H_nnp H_np
-- Derive our goal from a falsity
exact show p from False.elim H_false

-- Assuming p derive p
have H_p2p : p → p := by
intro (H_p : p)
exact show p from H_p

-- By proof by cases, we derive p
exact show p from Or.elim H_LEM H_p2p H_np2p


Alternatively for the tactic based approach.

example {p: Prop} (H_nnp : ¬¬p) : p := by
have H_LEM : p ∨ ¬p := LEM
cases' H_LEM with H_p H_np

-- Assuming p, derive p
case inl =>
exact show p from H_p

-- Assuming ¬p derive p
case inr =>
-- ¬p and ¬¬p are a direct contradiction
have H_false : False := H_nnp H_np
exact show p from False.elim H_false


Lean has this theorem built-in with Classical.not_not.

## First Order

Lean is also capable of reasoning over first order logic. In this section, we’ll start seeing objects/terms and predicates instead of just propositions.

For example {α : Type} {P : α → Prop}  means that $P$ is a predicate of arity one and takes an object of type $\alpha$.

### Forall Elim

If we have a forall statement, then we can replace the bound variable with an object of that type and remove the forall. Lets say for our example we have the following forall statement: $\forall x \in \mathbb{N}: x \ge 0$. Then we can replace the $x$ with $2$ and get the following formula: $2 \ge 0$.

example {α : Type} {P : α → Prop} {y : α} (H : ∀ x : α,  P x) : P y := by
exact show P y from H y


### Forall Intro

To show that some property holds for all $x$ of a type α, you need to show that it holds for an arbitrary $x$ of that type. We can introduce this object, by the intro command.

example {α : Type} {P Q R : α → Prop} (H_pq : ∀ x : α, P x → Q x) (H_qr : ∀ x : α, Q x → R x) : ∀ x : α, P x → R x := by
intro (y: α)
have H_pqx : P y → Q y := H_pq y
have H_qrx : Q y → R y := H_qr y
intro (H_py : P y)
have H_qy : Q y := H_pqx H_py
exact show R y from H_qrx H_qy


### Exists Intro

To introduce an existential, you need to show that the formula holds for any object of a certain type.

example {α : Type} {P : α → Prop} {y : α} (H: P y) : ∃ x: α, P x := by
exact show ∃ x, P x from Exists.intro y H


In the tactic based approach, this is done via exists:

example {α : Type} {P : α → Prop} {y : α} (H: P y) : ∃ x: α, P x := by
exact show ∃ x, P x from by exists y


### Exists Elim

Lets say we have the following forall statement: $\forall a \in \alpha: p a \implies b$.

Now lets say we have the following existential: $\exists x, p x$.

Using these, we can derive $b$.

example {α : Type} {p : α → Prop} {b : Prop} (H_epx : ∃ x, p x) (H_pab : ∀ (a : α), p a → b) : b := by
exact show b from Exists.elim H_epx H_pab


Alternatively for the tactic based approach:

example {α : Type} {p : α → Prop} {b : Prop} (H_epx : ∃ x, p x) (H_pab : ∀ (a : α), p a → b) : b := by
cases' H_epx with c H_pc
have H_pcb : p c → b := H_pab c
exact show b from H_pcb H_pc


## Inductive Types

One of the biggest use cases of an interactive theorem prover is in program verification. To help represent recursive data structures, we have the notion of an inductive type.

Let’s create a custom representation of a list. A list can either by empty (cnil) or be an element hd combined with the rest of some list tl.

inductive CustomList (T : Type) where
| cnil : CustomList T
| ccons (hd : T) -> (tl : CustomList T) : CustomList T


Some examples of a list here include cnil, ccons(0, cnil), and ccons(1, ccons(0, cnil)).

For convenience, we’ll open the CustomList namespace so that we don’t have to refer each constructor (cnil/ccons) by it.

open CustomList


### Functions over Inductive Types

To define a function over an inductive type, we need to cover each of the constructors.

For example, let’s consider the notion of a list’s length.

• If the list is cnil then the length is $0$.
• If the list starts with ccons then we add 1 to the length of the tail tl.
def clength {α : Type}:  CustomList α → Nat
| cnil => 0
| (ccons _ as) => 1 + clength as


We can see the output of a function via the #eval command.

#eval clength (@cnil Nat)
#eval clength (ccons 2 (ccons 1 cnil))


For another example, let us look at appending two lists. As an example if we have the list [1, 2, 3] and the list [4, 5, 6], then appending those two lists will create [1, 2, 3, 4, 5, 6].

def cappend {α : Type} (as bs : CustomList α) : CustomList α :=
match as with
| cnil => bs
| ccons a as => ccons a (cappend as bs)


Example evaluations, make sure these come out to what you expect.

#eval cappend (ccons 1 cnil) (ccons 2 cnil)
#eval clength (cappend (ccons 1 cnil) (ccons 2 cnil))


### Theorems over Inductive Types

Now that we have a data structure and some methods over it. We can now prove some interesting properties.

First let’s start off with the following theorem.

Appending cnil to a list as is equivalent to the list as.

When instantiating an inductive type, the inductive hypothesis is created for it via recOn. Therefore, we can rely on that for the proof.

theorem append_nil {α : Type} (as : CustomList α) : cappend as cnil = as := by
-- Base Case
have H_BASE : (cappend cnil cnil = (@cnil α)) := by rfl

-- Inductive Step
have H_Inducive : ∀ (hd : α) (tl : CustomList α), cappend tl cnil = tl → cappend (ccons hd tl) cnil = ccons hd tl := by
intro (hd : α)
intro (tl : CustomList α)
intro (IH : cappend tl cnil = tl)
calc
cappend (ccons hd tl) cnil = ccons hd (cappend tl cnil) := by rw [cappend]
_ = ccons hd tl := by rw [IH]

-- Apply induction principle
exact CustomList.recOn  (motive := fun x => cappend x cnil = x)
as
H_BASE
H_Inducive


The rewrite/rw command allows us to replace instances of functions with their definitions. The goal is to get both sides of the equality to be syntactically the same. The calc environment allows us to perform multiple rewrites in order to get closer to that end.

Instead of explicitly making use of recOn, we can use the induction tactic.

theorem append_nil2 {α : Type} (as : CustomList α) : cappend as cnil = as := by
induction as

case cnil =>
calc
cappend cnil cnil = cnil := by rw [cappend]
_ = cnil := by exact rfl

case ccons hd tl IH =>
calc
cappend (ccons hd tl) cnil = ccons hd (cappend tl cnil) := by rw [cappend]
_ = ccons hd tl := by rw [IH]


### Double Induction

For our next example, we’ll need to perform induction on two lists.

Given two lists as and bs. The length of their append is the same as the length of each individual list added together.

theorem length_append_sum {α : Type} (as bs : CustomList α) : clength (cappend as bs) = clength as + clength bs := by
induction as
induction bs

case cnil.cnil =>
calc
clength (cappend cnil cnil) = clength cnil := by rw [cappend]
_ = 0 := by rw [clength]
_ = 0 + 0 := by linarith
_ = (clength cnil) + (clength cnil) := by rw [clength]

case cnil.ccons hd tl _ =>
calc
clength (cappend cnil (ccons hd tl)) = clength (ccons hd tl) := by rw [cappend]
_ = 0 + clength (ccons hd tl) := by linarith
_ = clength cnil + clength (ccons hd tl) := by rw [clength]

case ccons hd tl IH =>
calc
clength (cappend (ccons hd tl) bs) = clength (ccons hd (cappend tl bs)) := by rw [cappend]
_ = 1 + clength (cappend tl bs) := by rw [clength]
_ = 1 + (clength tl + clength bs) := by rw [IH]
_ = (1 + clength tl) + clength bs := by linarith
_ = clength (ccons hd tl) + clength bs := by rw [clength]

-- Lean intelligently wlogs the fourth case


Notice that a couple times in the proof, make use of a tactic called linarith. This stands for “linear arithmetic” and helps solve goals involving numbers. I generally employ this rather than figuring out which definitions I need to perform commutativity and associativity rules.

## Conclusion

One of my favorite things about Lean is the ability to make proofs more readable by making use of the have, calc, and rewrite tactics. I do find it easier, however, to use the induction tactic for inductive proofs. Especially when dealing with nested inductions as writing out the cases explicitly can be daunting.

If you catch any mistakes in me converting this post, let me know. Otherwise feel free to email me if you have any questions.

Lastly, I want to give my thanks to James Oswald for helping proofread this post and making it better.

Was this useful? Feel free to share: Hacker News Reddit Twitter

Published a response to this? :